Analisis Romantisme dalam Empat Kumpulan Sajak Kakawin Kawin Karya Ws Rendra - Ngifat Khoerunnisa; Adina Anisnaeni Rizqina; Arinda Oktariski Setyaningsih; Azizah Nur Imani; Edy Suryanto (CV. Alim's Publishing, 2023)
Every literary work has a message and meaning contained so that every reader can take lessons from the work, one of which is poetry. The purpose of this research is to analyze the elements or symbols of romance found in the Four Collections of Poetry by WS Rendra. The method used in this research is descriptive qualitative method. The data sources used came from a book entitled Four Collections of Poetry in the Romance section of the Kakawin Kawin chapter by WS Rendra, namely (1) Love Letters; (2) Green Serenada; (3) Blue Serenada; (4) Episodes; (5) Serenade Violet; (6) Under the Moon; (7) White Serenade; (8) Black Serenade; (9) Gray Serenada, (10) Red Serenada; and (11) Letter to Mother: About Her Prospective Son-in-law. While the data sought is a symbol of romance. Data collection was carried out by document analysis using the method of taking notes and literary analysis, while to test the validity of the data using theoretical triangulation techniques. The results of this study found that there are various romantic symbols in the book entitled Four Collections of Poetry in the Kakawin Kawin chapter Romance section by WS Rendra.